Polyurethane polishing pad and preparation method thereof
By using modified abrasives in the polyurethane polishing pad, the problem of scratches and uneven polishing during long-term use is solved, and the self-treatment function and efficient polishing effect of the polyurethane polishing pad are achieved.
Patent Information
- Application Number
- CN202510050526.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
Existing polyurethane polishing pads are prone to scratches and uneven polishing problems during long-term use, which affects its service life and polishing effect.
By using modified abrasives, the modified abrasives such as cerium oxide, zirconia and alumina with silane coupling agent, dimer acid diglycidyl ester and 4-hydroxybutyl vinyl ether, the prepared modified abrasives have good compatibility and dispersion with the polyurethane system, forming a polyurethane polishing pad with a compact and uniform molecular structure.
Modified abrasives significantly improve the self-treatment function of the polyurethane polishing pad, avoid surface wear and clogging, extend service life, and improve polishing efficiency and smoothness, reducing scratches and uneven problems.
Smart Images

Figure BDA0005239825790000051 
Figure BDA0005239825790000061 
Figure BDA0005239825790000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of polyurethane polishing materials, and more specifically, to a polyurethane polishing pad and a preparation method thereof. Background Art
[0002] Chemical mechanical polishing (CMP) technology is one of the key technologies for surface processing of semiconductor wafers. In the CMP process, the polishing pad, as one of the key consumables, has the functions of storing and transporting polishing liquid, removing processing residual materials, transmitting mechanical loads and maintaining the polishing environment. However, as the polishing continues, the polishing pad undergoes surface wear and matrix compression, gradually becomes smooth, and forms a glaze surface. In addition, the grooves on the surface of the polishing pad used to distribute the polishing liquid and remove the waste liquid are gradually filled with polishing residues and polishing powder particles, resulting in a decrease in the polishing pad's ability to store and transport abrasives. In order to solve the above problems, the polishing pad must be trimmed to improve the polishing effect and increase its service life. At present, conventional dressing technologies for polishing pads can be divided into two categories: self-dressing technology and non-self-dressing technology.
[0003] Among them, the polyurethane polishing pad with abrasive generally has a self-dressing function. During the preparation process of this polyurethane polishing pad, the abrasive is dispersed into the polishing pad. During the polishing process, the abrasive automatically separates from the surface of the polishing pad by means of the friction between the polishing pad and the polishing material. At the same time, the surface of the polishing pad will also be appropriately worn, thereby exposing the abrasive inside the polishing pad, so that the polyurethane polishing pad has a better automatic repair function.
[0004] The above-mentioned polyurethane polishing pads are generally used for grinding and polishing of sapphire optics, silicon carbide wafer metal and glass materials, and are used for high flatness fine polishing processes, which requires high grinding uniformity and scratch resistance of polyurethane polishing pads. Existing polyurethane polishing pads are prone to scratches and uneven polishing during long-term polishing, which needs to be solved. Summary of the invention
[0005] In order to solve the problem that the existing polyurethane polishing pad is prone to scratches and uneven polishing during long-term polishing, the present application provides a polyurethane polishing pad and a preparation method thereof.
[0006] In a first aspect, the present application provides a polyurethane polishing pad, which adopts the following technical solution: A polyurethane polishing pad is prepared from the following raw materials in parts by weight: 35-45 parts of diisocyanate Polycarbonate polyol 15-20 parts Polyether polyol 8-14 parts Modified abrasive 50-60 parts Chain extender 4-8 parts Catalyst 2-4 parts Foaming agent 0.5-1.5 parts 1-3 parts of antioxidants; The modified abrasive is prepared from abrasive, a silane coupling agent, dimer acid diglycidyl ester and 4-hydroxybutyl vinyl ether; the abrasive is a combination of at least two of cerium oxide, zirconium oxide and / or aluminum oxide.
[0007] By adopting the above technical scheme, the polyurethane polishing pad of the present application can maintain good polishing efficiency and flatness during long-term use, effectively avoiding the problems of scratches and uneven polishing. The polyurethane polishing pad with good hardness and flexibility is prepared by using diisocyanate to provide isocyanate groups, polycarbonate polyol, polyether polyol and chain extender to provide hydroxyl groups for reaction, and adding modified abrasives to the polyurethane system, wherein the modified abrasives are composed of at least two combinations of cerium oxide, zirconium oxide and / or aluminum oxide as the main body, and the abrasives are modified by using silane coupling agent, dimer acid diglycidyl ester and 4-hydroxybutyl vinyl ether, and the prepared modified abrasives have good compatibility and dispersibility with the polyurethane system, and can be further cross-linked and interwoven with the polyurethane system, so as to prepare a polyurethane polishing pad with good molecular structure compactness and uniform system, and the polyurethane polishing pad can continuously expose uniformly dispersed new abrasives during the polishing process, thereby ensuring a stable polishing effect, and is particularly suitable for fine grinding and polishing of sapphire optics, silicon carbide wafer metal and glass materials, and can achieve a mirror effect.
[0008] Preferably, the silane coupling agent is composed of a long straight-chain alkyl silane coupling agent and 3-isocyanate propyltrimethoxysilane in a weight ratio of 1:(2-3).
[0009] By adopting the above technical solution, using a long straight-chain alkyl silane coupling agent and 3-isocyanate propyl trimethoxy silane in a relatively optimal weight ratio as a silane coupling agent, the compatibility between the abrasive and the polyurethane system can be significantly improved, thereby improving the overall strength and wear resistance uniformity of the polishing pad. The long straight-chain alkyl silane coupling agent refers to a long-chain silane coupling agent with dodecyl to octadecyl groups, which has good interweaving and dispersion properties and can produce good synergistic effects with 3-isocyanate propyl trimethoxy silane, so that the abrasive is evenly interwoven and dispersed in the polyurethane system, thereby improving the long-term polishing uniformity, stability and flatness during the polishing process.
[0010] Preferably, the modified abrasive is prepared from the following raw materials in parts by weight: Abrasive 80-100 parts Silane coupling agent 5-8 parts 4-6 parts of dimer acid diglycidyl ester 3-5 parts of 4-hydroxybutyl vinyl ether.
[0011] Preferably, the modified abrasive is prepared by the following steps: The abrasive, silane coupling agent, dimer acid diglycidyl ester and 4-hydroxybutyl vinyl ether are added into a kneading device, and the temperature is raised to 60-80° C. for kneading and dispersion to obtain a modified abrasive.
[0012] By adopting the above technical scheme, the component dosage and preparation process of the modified abrasive are further optimized, and the prepared modified abrasive has good dispersion uniformity with the polyurethane system, thereby enhancing the overall mechanical properties and wear resistance of the prepared polyurethane polishing pad. The silane coupling agent can couple with the abrasive to increase the dispersion spacing between the abrasive particles, and the dimer acid diglycidyl ester and 4-hydroxybutyl vinyl ether can play a good synergistic role with the silane coupling agent to form a uniformly dispersed film on the surface of the abrasive, and under the action of the hydroxyl group, it can further cross-link with the polyurethane system, improve the dispersion uniformity of the abrasive in the polyurethane system, reduce the agglomeration phenomenon, and then improve the stability and flatness of the polishing effect, and reduce the problems of scratches and unevenness.
[0013] Preferably, the abrasive is composed of cerium oxide, zirconium oxide and aluminum oxide in a weight ratio of (2-3):(1-2):5.
[0014] By adopting the above technical solution, cerium oxide has high toughness and wear resistance, can provide excellent polishing uniformity and prevent scratches; zirconium oxide and aluminum oxide have excellent hardness and cutting performance, can further provide excellent cutting ability and polishing efficiency. The three are compounded in an optimal weight ratio, which not only improves the overall performance of the polyurethane polishing pad, but also ensures the uniformity and stability during the polishing process.
[0015] Preferably, the chain extender is composed of trimethylolpropane and castor oil modified polyol in a weight ratio of (3-4):1.
[0016] By adopting the above technical solution, trimethylolpropane and castor oil modified polyol are used as chain extenders in an optimal weight ratio. The crosslinking density of the polyurethane system can be further improved, a network molecular structure can be formed, and the dispersion uniformity of the modified abrasive can be further improved, thereby improving the prepared polyurethane polishing pad to maintain a good polishing effect and flatness during long-term use, avoiding scratches and uneven polishing problems.
[0017] Preferably, the catalyst is composed of an organic tin catalyst, an amine catalyst and trimethylhydroxyethyl bisaminoethyl ether in a weight ratio of 1:(0.2-0.4):(0.5-0.8).
[0018] By adopting the above technical scheme, using an organic tin catalyst, an amine catalyst and trimethylhydroxyethyl bisaminoethyl ether in a preferred weight ratio as a catalyst, while improving the catalytic activity of the polyurethane system and accelerating the reaction process, the foaming uniformity of the system can also be further improved. If the curing is too fast, the foaming rate of the system is low, and if the curing is too slow, the foaming of the system is prone to unevenness.
[0019] Preferably, the foaming agent is water, and the antioxidant is antioxidant 1010 and / or antioxidant 168.
[0020] By adopting the above technical solution and using water as a foaming agent, a good foaming effect can be achieved at a relatively low cost. Selecting antioxidant 1010 and / or antioxidant 168 as an antioxidant can effectively prevent the aging problem of the polyurethane polishing pad during long-term use and extend the service life of the polishing pad.
[0021] In a second aspect, the present application provides a method for preparing a polyurethane polishing pad, using the following technical solution: A method for preparing a polyurethane polishing pad comprises the following steps: S1, uniformly mixing diisocyanate, polycarbonate polyol, polyether polyol, chain extender, modified abrasive, catalyst, foaming agent and antioxidant to prepare a mixture; S2, injecting the mixture into a mold, heating it to perform a foaming reaction, and obtaining a foamed polyurethane; S3, ripening the foamed polyurethane to obtain a polyurethane polishing pad.
[0022] By adopting the above technical solution, the polyurethane polishing pad prepared by the preparation method of the present application has high polishing stability and flatness, and can effectively avoid the problems of scratches and uneven polishing.
[0023] Preferably, the reaction temperature in step S2 is 85-95° C., and the reaction time is 1.5-2.5 h.
[0024] By adopting the above technical solution, the time and temperature of the reaction foaming are optimized, ensuring the full progress of the foaming process and further improving the structural stability of the polyurethane polishing pad.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. By adding modified abrasives to the polyurethane polishing pad, the self-dressing function of the polishing pad is significantly improved, which effectively solves the problem of surface wear and clogging after long-term use and extends the service life of the polishing pad; 2. The introduction of modified abrasives enhances the grinding uniformity and anti-scratch performance of the polishing pad, which is particularly suitable for fine grinding and polishing of sapphire optics, silicon carbide wafers, metals and glass materials, ensuring a high-flatness mirror effect; 3. The polishing pad can maintain good polishing efficiency and flatness during long-term use, reducing product quality problems caused by uneven polishing and scratches, and improving production efficiency. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments.
[0027] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used: 1. Cerium oxide: particle size 100-200nm; 2. Zirconia: particle size 100-200nm; 3. Alumina: particle size 50-100nm; 4. Dimer acid diglycidyl ester: brand: Kamik, CAS number: 68475-94-5, content: 99%; 5. Castor oil modified polyol: Ito, URIC AC009.
[0028] Preparation example of modified abrasive Preparation Example 1 Preparation Example 1 discloses a modified abrasive, which is prepared by the following steps: 8 kg of abrasive (composed of cerium oxide and aluminum oxide in a weight ratio of 1:1), 0.5 kg of silane coupling agent (composed of vinyl trimethoxy silane coupling agent and 3-isocyanate propyl trimethoxy silane in a weight ratio of 1:2), 0.4 kg of dimer acid diglycidyl ester and 0.5 kg of 4-hydroxybutyl vinyl ether were added to a kneader, the temperature was raised to 60°C and kneading and dispersion were performed for 2 hours to obtain a modified abrasive.
[0029] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.
[0030] Table 1 Parameters of Preparation Examples 1-3 Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the abrasive is composed of cerium oxide, zirconium oxide and aluminum oxide in a weight ratio of 2:1:5, and the rest is the same as Preparation Example 1.
[0031] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that the abrasive is composed of cerium oxide, zirconium oxide and aluminum oxide in a weight ratio of 3:2:5, and the rest is the same as Preparation Example 1.
[0032] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 5 is that the silane coupling agent is composed of dodecyltrimethoxysilane and 3-isocyanatepropyltrimethoxysilane in a weight ratio of 1:2, and the rest is the same as Preparation Example 5.
[0033] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 5 is that the silane coupling agent is composed of dodecyltrimethoxysilane and 3-isocyanatepropyltrimethoxysilane in a weight ratio of 1:3, and the rest is the same as Preparation Example 5.
[0034] Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that an equal amount of dimer acid diglycidyl ester is replaced by 4-hydroxybutyl vinyl ether, and the rest is the same as Preparation Example 1.
[0035] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 1 is that 4-hydroxybutyl vinyl ether is replaced by an equal amount of dihydroxy polyether, model N210, molecular weight 1000, and the rest is the same as Preparation Example 1. Example
[0036] Example 1 Example 1 discloses a polyurethane polishing pad, which is prepared by the following steps: S1, 3.5kg of diisocyanate (composed of isophorone diisocyanate and diphenylmethane diisocyanate in a weight ratio of 1:2), 1.5kg of polycarbonate diol as polycarbonate polyol, 0.8kg of polytetramethylene ether glycol as polyether polyol, 0.4kg of chain extender (composed of trihydroxypropane and castor oil modified polyol in a weight ratio of 3:1), 5kg of modified abrasive prepared in Preparation Example 1, 0.2kg of catalyst (composed of dibutyltin dilaurate, triethylenediamine and trimethylol hydroxyethyl bisaminoethyl ether in a weight ratio of 1:0.2:0.5), 0.05kg of water as a foaming agent and 0.1kg of antioxidant 1010 were uniformly mixed to prepare a mixture; S2. Inject the mixture into a mold, raise the temperature to 85°C for foaming reaction, and foam for 2.5 hours to obtain foamed polyurethane.
[0037] S3. Ripening the foamed polyurethane at 55° C. for 24 hours to obtain a polyurethane polishing pad.
[0038] The molecular weight of polytetramethylene ether glycol is 2000-3000; the molecular weight of polycarbonate diol is 2000-3000; Example 2-3 The difference between Example 2-3 and Example 1 is that the amount of raw materials used and the preparation process parameters are different, see Table 2 below for details.
[0039] Table 2 Parameters of Examples 1-3 Example 4 The difference between Examples 4-7 and Example 1 is that the sources of the modified abrasive are different, see Table 3 below for details.
[0040] Table 3 Sources of modified abrasives of Examples 4-7 Example Sources of modified abrasives Example 4 Preparation Example 4 Example 5 Preparation Example 5 Example 6 Preparation Example 6 Example 7 Preparation Example 7 Example 8 The difference between Example 8 and Example 1 is that an equal amount of trimethylhydroxyethylbisaminoethyl ether is replaced by bisdimethylaminoethyl ether, and the rest is the same as Example 1.
[0041] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the modified abrasive is derived from the preparation of Comparative Example 1, and the rest is the same as Example 1.
[0042] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the modified abrasive is derived from the preparation of Comparative Example 2, and the rest is the same as Example 1.
[0043] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the dimer acid diglycidyl ester and 4-hydroxybutyl vinyl ether are replaced by silane coupling agent in equal amounts, and the rest are the same as Example 1.
[0044] Performance testing The following is a performance test of the polyurethane polishing pads prepared in Examples 1-8 and Comparative Examples 1-3. A polyurethane polishing pad with a thickness of 5 mm is used as the test sample: 1. Hardness test Test the hardness (unit: A) according to the standard method of GB / T2411-2008, and record the test results; 2. Long-term polishing stability test Polishing equipment: surface grinding and polishing machine; Polishing equipment parameters: the upper polishing disc speed is 30r / min, the lower polishing disc speed is 30r / min, and the polishing pressure is 5KPa; the material to be polished: silicon carbide wafer, diameter 100mm, thickness 500μm; Polishing liquid: silicon oxide polishing liquid, commercially available Jizhi brand; The polishing liquid was diluted with deionized water to 15wt% and used, and the flow rate of the polishing liquid was controlled to be 260ml / min, and the silicon carbide wafer was polished. The polishing time of a single silicon carbide wafer was 5min. The long-term polishing test was carried out with this polishing parameter. After the polyurethane polishing pad was used for 12h, the silicon carbide wafer was polished again. The polishing rate of the polyurethane polishing pad and the scratch condition of the silicon carbide wafer surface after polishing were tested, and the test results were tested and recorded. The calculation formula for the polishing rate (unit: nm / min) is: polishing rate = (thickness before polishing - thickness after polishing) / polishing time; the scratch scoring is as follows: no scratches, recorded as level 0; 1-3 scratches, recorded as level 1; 4-6 scratches, recorded as level 2; 6-10 scratches, recorded as level 3; 11-15 scratches, recorded as level 4; 16 or more scratches and level 5.
[0045] The following are the performance test data of the polyurethane polishing pads of Examples 1-8 and Comparative Examples 1-3, see Table 4 below for details.
[0046] Table 4 Performance data of Examples 1-8 and Comparative Examples 1-3 Combining Examples 1-3 and Examples 4-7 and Comparative Examples 1-3 and Table 4, it can be concluded that the polyurethane polishing pad prepared using the modified abrasive of the present application has moderate hardness and flexibility, good polishing stability and uniformity, and is not prone to scratches. Compared with Example 1, Examples 4-5 optimize the abrasive, and compared with Example 5, Examples 6-7 further optimize the type of silane coupling agent, and the flexibility of the polyurethane polishing pad prepared is improved, while the hardness is slightly reduced, the polishing rate is increased, and the scratches are reduced. This may be because the compounding of the abrasive type and the selection of the silane coupling agent have a good synergistic effect, so that the abrasive can be evenly dispersed in the prepared polyurethane polishing pad, reducing the problem of abrasive aggregation, while improving the hardness. Increase the polishing rate and reduce the occurrence of scratches. In Comparative Example 1-2, the components of dimer acid diglycidyl ester and 4-hydroxybutyl vinyl ether were changed, and in Comparative Example 3, only silane coupling agent was used to modify the abrasive. The hardness of the obtained polyurethane polishing pad was significantly improved, but the polishing rate was also significantly reduced, and obvious scratches appeared. This may be because dimer acid diglycidyl ester, 4-hydroxybutyl vinyl ether and silane coupling agent can play a good synergistic role. The obtained modified abrasive is applied to the polyurethane polishing pad, which can significantly improve the dispersion and compatibility of the modified abrasive, thereby improving the flexibility of the polyurethane polishing pad while increasing the polishing rate; the reduced polishing rate in the comparative example may be because although the hardness is improved, the abrasive is unevenly dispersed, which affects the polishing rate.
[0047] Combining Example 1 and Example 8 with Table 4, it can be concluded that the use of an optimal weight ratio of an organic tin catalyst, an amine catalyst and trimethylhydroxyethyl bisaminoethyl ether as a catalyst can improve the catalytic stability of the present application, thereby improving the foaming uniformity of the prepared polyurethane polishing pad, so that the polyurethane polishing pad has a moderate hardness while having a good polishing rate and polishing stability.
[0048] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A polyurethane polishing pad, characterized in that: Made from the following raw materials in parts by weight: 35-45 parts of diisocyanate Polycarbonate polyol 15-20 parts Polyether polyol 8-14 parts Modified abrasive 50-60 parts Chain extender 4-8 parts Catalyst 2-4 parts Foaming agent 0.5-1.5 parts 1-3 parts of antioxidants; The modified abrasive is prepared from abrasive, a silane coupling agent, dimer acid diglycidyl ester and 4-hydroxybutyl vinyl ether; the abrasive is a combination of at least two of cerium oxide, zirconium oxide and / or aluminum oxide.
2. A polyurethane polishing pad according to claim 1, characterized in that: The silane coupling agent is composed of a long straight-chain alkyl silane coupling agent and 3-isocyanate propyltrimethoxysilane in a weight ratio of 1:(2-3).
3. A polyurethane polishing pad according to claim 1 or 2, characterized in that: The modified abrasive is prepared from the following raw materials in parts by weight: Abrasive 80-100 parts Silane coupling agent 5-8 parts 4-6 parts of dimer acid diglycidyl ester 3-5 parts of 4-hydroxybutyl vinyl ether.
4. A polyurethane polishing pad according to claim 3, characterized in that: The modified abrasive is prepared by the following steps: Add the abrasive, silane coupling agent, dimer acid diglycidyl ester and 4-hydroxybutyl vinyl ether into a kneading device, heat to 60-80° C. for kneading and dispersion, and obtain the modified abrasive.
5. The polyurethane polishing pad according to claim 3, characterized in that: The abrasive material is composed of cerium oxide, zirconium oxide and aluminum oxide in a weight ratio of (2-3):(1-2):
5.
6. The polyurethane polishing pad according to claim 1, characterized in that: The chain extender is composed of trimethylolpropane and castor oil modified polyol in a weight ratio of (3-4):
1.
7. The polyurethane polishing pad according to claim 1, characterized in that: The catalyst consists of an organic tin catalyst, an amine catalyst and trimethyl hydroxyethyl bisaminoethyl ether in a weight ratio of 1:(0.2-0.4):(0.5-0.8).
8. The polyurethane polishing pad according to claim 1, characterized in that: The foaming agent is water, and the antioxidant is antioxidant 1010 and / or antioxidant 168.
9. A method for preparing a polyurethane polishing pad according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, uniformly mixing diisocyanate, polycarbonate polyol, polyether polyol, chain extender, modified abrasive, catalyst, foaming agent and antioxidant to prepare a mixture; S2, injecting the mixture into a mold, heating it to perform a foaming reaction, and obtaining a foamed polyurethane; S3, ripening the foamed polyurethane to obtain a polyurethane polishing pad.
10. The method for preparing a polyurethane polishing pad according to claim 9, characterized in that: The reaction temperature in step S2 is 85-95° C., and the reaction time is 1.5-2.5 h.
Citation Information
Cited By
Chemical mechanical polishing pad and preparation method and application thereof
CN120680426A
Wear-resistant polyurethane polishing layer for SiC wafer as well as preparation method and application of wear-resistant polyurethane polishing layer
CN121343177A